A study on student’s spending behavior among part six students in UiTM Malacca City Campus / Norhafizah Abu Hassan and Nurul Atiqah Manap - Abu Hassan, Norhafizah; Manap, Nurul Atiqah (Faculty of Administrative Science and Policy Studies, 2012)
Study loan were given to students in the tertiary education level to make sure that students can further their study without facing any financial problems. So, the students need to manage their study loans wisely. The students must use the money for educational and necessity only. If they spend money on non-necessity, the money will not be enough. This study was conducted to know whether the students spend their study loan for necessity or non-necessity and also to study the factor that affect the students spending behavior. In this study, we use stratified sampling technique and distribute the questionnaire to respondents which are Part Six students of UiTM Malacca City Campus. From the findings of this survey, the students spend their money more on necessity things rather than non-necessity things. It means that the students shown a good spending behavior. From the findings also tells that self control are the main factors that lead to good spending behavior. In conclusion, we can conclude that the students spend their study loan for necessity rather than non-necessity which shows the students have a good spending behavior.